2022
DOI: 10.1186/s12967-022-03734-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MAP3K4 as a novel regulation factor of hepatic lipid metabolism in non-alcoholic fatty liver disease

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is a metabolic disorder with abnormal lipid metabolism. The present study was to identify regulatory genes related to lipid droplets (LDs) abnormal accumulation in NAFLD. Methods transcriptomic analysis and bioinformatics analysis (GEO database) were used to identify potential genes in abnormal lipid metabolism of NAFLD. A candidate gene MAP3K4 expression were detected by immunohistochemistry sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Immune disorders, intestinal imbalances, and metabolic disorders promote liver inflammation and other aspects during late-stage NAFLD [ 9 ]. A study has shown that inflammation and metabolic processes in adipose tissue could accelerate NASH development and serve as therapeutic targets [ 10 ]. In fact, some studies have suggested that NAFLD could be referred to as metabolic (dysfunction) associated fatty liver disease (MAFLD) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune disorders, intestinal imbalances, and metabolic disorders promote liver inflammation and other aspects during late-stage NAFLD [ 9 ]. A study has shown that inflammation and metabolic processes in adipose tissue could accelerate NASH development and serve as therapeutic targets [ 10 ]. In fact, some studies have suggested that NAFLD could be referred to as metabolic (dysfunction) associated fatty liver disease (MAFLD) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that CAMK2 regulates adipocyte lipolysis and its activity is increased in obese mice adipose tissue, which makes it a critical component of metabolic regulation in obesity 52 . Vital role of MAP3K4 (as an important member of the MAPK signaling pathway) in the hepatic lipogenesis of non-alcoholic fatty liver disease has been well described 53 . The expression of other important member of MAPK in the final DAS genes, MAP4K4, is reported to be increased during obesity, which makes it an important negative regulator of adipose lipogenesis in metabolic disease 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent report described an independent role for the Zak gene in promoting stem cell plasticity in the small intestine of leucine-restricted mice ( 73 ). Further adding to the complexity of our current mouse model, the ZAKβ isoform is activated by volumetric cell compression and protects against muscle pathology in mice and humans ( 49 , 74 ), and this splice variant is also interrupted in the whole-body ZAK KO animals. For the present study, generation of mouse models for conditional KO of the Zakα isoform was not achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we do not know to what extent our findings in mice can be extrapolated to humans. Patients with nonsense mutations in the common kinase domain of ZAKα and ZAKβ present with severe early-onset myopathy but with no reports of phenotypes of a metabolic nature ( 74 ). However, the feeding paradigm for mice used in this study is generally considered a good model of human obesity and associated metabolic complications.…”
Section: Discussionmentioning
confidence: 99%